Hydroxyapatite Synthesis from Fish Bones: Atlantic Salmon (Salmon Salar) - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
Production of the bioceramics on the market is presently conducted from typical precipitation method by using reagent grade raw chemicals or through calcination of natural sources like animal bones ( especially bovine bone) and fish bones. Usually fish bones were damped near or in the water sources, which can lead to serious environmental pollution. Those were regarded as a trash, even though they still bear economic value, including conjugates. In this study bones of Atlantic Salmon (Salmo salar) were used as a bioceramic material source. Bones of Atlantic Salmon were collected from Besiktas Fish Market. Those were cleaned from possible flesh with reagent grade NaOH. Cleaned parts were washed with demineralized water very neatly. Dry fish bones were calcinated at 850 degrees C for 4 hours. The obtained hydroxyapatite material was characterized with scanning electron microscopy and X-ray diffraction methods. It was found that the bioceramic material consisted of hydroxyapatite and various related phases. Scanning electron microscopy studies have revealed nano-structured bioceramic particles. The aim of this study is to obtain nano-structured bioceramics from bones of Atlantic Salmon in an environmentally friendly and economic way.